2020
DOI: 10.1186/s12891-020-03706-3
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for predicting overall survival in patients with Ewing sarcoma: a SEER-based study

Abstract: Background Ewing sarcoma, the second most frequent bone tumor in children and adolescents, is often presented with localized disease or metastatic-related symptoms. In this study, we aim to construct and validate a nomogram for patients with Ewing sarcoma to predict the 3- and 5-year overall survival (OS) based on the Surveillance, Epidemiology, and End Results (SEER) database. Methods Demographic and clinic pathological characteristics of patients with Ewing sarcoma diagnosed between 2010 and 2015 were extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Previous studies reported that ES’s potential clinical prognostic factors included age, race, tumour size, tumour stage and surgery 11 , 14 , 15 . However, these studies included a small number of predictors, which is prone to overfitting or biased fitting, resulting in different conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that ES’s potential clinical prognostic factors included age, race, tumour size, tumour stage and surgery 11 , 14 , 15 . However, these studies included a small number of predictors, which is prone to overfitting or biased fitting, resulting in different conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Nomogram was much more convenient to obtain the predictors. Hence, it was considered a big advantage over traditional staging, which had been proposed as an alternative and even a new standard to guide the treatment of cancer patients ( 17 , 28 , 29 ). We screened the clinical information of 929 patients with ES using a SEER database and found that survival time, race, T stage, M stage, surgery, and lung metastasis were significant factors that affected lymphatic metastasis in ES patients.…”
Section: Discussionmentioning
confidence: 99%
“…As a prediction model based on independent factors of clinical prognosis, nomogram has good stability and applicability ( 15 , 16 ). Therefore, it has been widely used to evaluate tumor prognosis and metastasis ( 17 21 ). Likewise, it can be used to predict and evaluate the prognosis of patients with ES.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, nomograms, developed using the SEER database, have been widely used to predict the prognosis of various malignancies, such as Ewing sarcoma, penile carcinoma, and cardiac sarcoma [ 23 25 ]. Our current study was the first to construct a well‐validated nomogram including several clinical features and risk scores for patients with PBS, which can predict the clinical prognosis of PBS intuitively and effectively.…”
Section: Discussionmentioning
confidence: 99%